2017
DOI: 10.1186/s12913-017-2296-y
|View full text |Cite
|
Sign up to set email alerts
|

Identified obstacles and prerequisites in telenurses’ work environment – a modified Delphi study

Abstract: BackgroundTelenursing is an expanding part of healthcare, staffed with registered nurses whose work environment is typical of a call centre. Work-related stress has been shown to be a major problem in nurses’ work environments and of importance to the outcome of care, patient safety, nurse job satisfaction and burnout. Today, however, we have a limited understanding of and knowledge about the work environment for telenurses. The aim of the present study is to explore and reach consensus on perceived important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…Despite the available research on difficult conversations in healthcare services, it has been found that factors in telenursing can also create communication difficulties. Communication between telenurses and callers can be affected by, for example, stress, multitasking and understaffing (Röing & Holmström, ), demanding workloads, cognitive fatigue and having no opportunity for recovery during the work shift (Bjorkman, Engstrom, Olsson, & Wahlberg, ), and frequent callers who increase the workload (Holmström, Krantz, Karacagil, & Sundler, ). Furthermore, telenurses find it problematic to handle callers’ questions related to their sick leave entitlement (Lännerström, von Celsing, Holmström, & Wallman, ), which is related to them being gatekeepers and having to balance conflicting demands from patients, coworkers and the organization (Lännerström, Wallman, & Söderbäck, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the available research on difficult conversations in healthcare services, it has been found that factors in telenursing can also create communication difficulties. Communication between telenurses and callers can be affected by, for example, stress, multitasking and understaffing (Röing & Holmström, ), demanding workloads, cognitive fatigue and having no opportunity for recovery during the work shift (Bjorkman, Engstrom, Olsson, & Wahlberg, ), and frequent callers who increase the workload (Holmström, Krantz, Karacagil, & Sundler, ). Furthermore, telenurses find it problematic to handle callers’ questions related to their sick leave entitlement (Lännerström, von Celsing, Holmström, & Wallman, ), which is related to them being gatekeepers and having to balance conflicting demands from patients, coworkers and the organization (Lännerström, Wallman, & Söderbäck, ).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, the investigations showed that organizational factors such as high workload (n = 6) contributed to the medical error reported in the malpractice claims, but measures targeting the organization were sparse (n = 1). Several studies performed within the context of telephone nursing have pointed out how telephone nursing is perceived as stressful work (35,44,45). In an interview study, (39) the telephone nurses who had been exposed to a malpractice claim revealed how always being aware of the number of calls waiting, and always feeling the pressure of organizational goals, could result in premature termination of calls.…”
Section: Discussionmentioning
confidence: 99%
“…Other aspects of the telephone nurses' work environment may pose a threat to patient safety. As shown, (45,46) disturbing background sound caused by callers (46) and disturbing sounds from other colleagues due to insu cient workplace soundproo ng (45) might disturb the communication. Within the context of nursing, work environment has also shown to be of importance to the outcome of care, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbing sounds in the surrounding environment and having to rely on external technical support were also described as negatively impacting on the telenurses’ nursing care performance. Note that the problem of lack of technical support was described almost 10 years ago (Ernesäter, Holmström, & Engström, ), and it seems that the problem has not been addressed, as technical issues were ranked second among the problems in telenurses’ work environment (Bjorkman et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In many Western countries (the UK, Denmark, Sweden, the USA, Holland), telephone advice nursing (henceforth telenursing) is citizens' first contact with healthcare services. The service is staffed by registered nurses who triage care-seekers' need for care using a computerised decision support system (Andersson-Bäck, 2008;Bishop, 2008;Blank et al, 2012). Telenursing is regarded as highly qualified nursing care, and providing care via the telephone is considered a complex form of nursing (Greenberg, 2009;Snooks et al, 2008).…”
Section: Introductionmentioning
confidence: 99%